[P291] Comparison of beam model implementation methods for commissioning of Monte Carlo code in proton beam therapy centre. (August 2018) - Garbacz, Magdalena; Gajewski, Jan; Krah, Nils; Schiavi, Angelo; Skrzypek, Agata; Rucinski, Antoni
Abstract : Purpose: In proton beam therapy (PBT), Monte Carlo (MC) methods offer more accurate dose recalculation than analytical treatment planning system (TPS) used in clinical routine. The purpose of this work was to implement a PBT centre beam model in MC code. This is essential when employing the code as a support tool for quality assurance procedures and using data from MC simulation as an additional information for the clinical TPS. Furthermore, different beam implementation methods were compared in order to find the most adequate approach to simulate beam source and obtain the best agreement between MC simulations and TPS. Methods: Simulations of proton pencil beams in water phantom were performed in order to find MC specific beam parameters that characterize the beam model in the PBT centre. A GPU-accelerated MC code was used, which significantly reduces the dose distribution calculation time. Two beam model implementation methods were considered: (i) a paraxial beam approach and (ii) an emittance model. The paraxial beam approach is determined from depth-dose-distribution (DDD) measurements and TPS calculations in a water phantom. The emittance model additionally accounts for the measurement of beam profiles in air. The beam shape and dose values for single beam simulations using the two methods were compared with TPS, which was used as a reference. Results: A perfect agreement in beam range, within binning uncertainty of 0.1 mm, was obtained for single beam DDDs calculated with MC code and TPS comparing both beam model implementation approaches. The simulated lateral beam size fit to TPS reference values for the paraxial beam approach and emittance model differing up to 10% (delta_sigma < 0.5 mm). The minor difference of up to 0.2 mm in the beam size was observed between the emittance model and the paraxial beam approach. Conclusions: The preliminary results showed that the beam size in the water phantom for the paraxial beam approach, the emittance model and TPS are in good agreement, even though, the emittance model considers actual variation of the beam size in air. For the clinical application these findings must be further verified by MC simulations and experimentally.